2012
DOI: 10.1128/jcm.06169-11
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of a Real-Time PCR Assay for Rapid Identification of Staphylococcal Bacteremia

Abstract: The purpose of this study was to evaluate the impact of real-time PCR reporting both on timely identification of clustered Grampositive cocci (GPC) in blood cultures and on appropriate antibiotic treatment. This retrospective, interventional cohort study evaluated inpatients with blood cultures positive for GPC in the pre-PCR (15 January 2009 to 14 January 2010) and post-PCR (15 January 2010 to 14 January 2011) periods. Post-PCR implementation, laboratory services completed batched PCR; results other than meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
87
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 14 publications
0
87
1
2
Order By: Relevance
“…However, this may be dependent on the method of communication with the provider. While Bauer et al (6) showed improvements in some of these areas with rapid notification of an infectious disease pharmacist in addition to the provider, Frye et al (4) showed no improvement in their outcome measures by releasing the results of a rapid molecular S. aureus/MRSA test into the electronic medical record, even though there was a statistically significant decrease in the time before results were available. Similarly, Carver et al showed that clinicians failed to utilize rapid mecA test results on positive blood cultures without the intervention of an infectious disease pharmacist (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, this may be dependent on the method of communication with the provider. While Bauer et al (6) showed improvements in some of these areas with rapid notification of an infectious disease pharmacist in addition to the provider, Frye et al (4) showed no improvement in their outcome measures by releasing the results of a rapid molecular S. aureus/MRSA test into the electronic medical record, even though there was a statistically significant decrease in the time before results were available. Similarly, Carver et al showed that clinicians failed to utilize rapid mecA test results on positive blood cultures without the intervention of an infectious disease pharmacist (16).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies that analyzed rapid diagnostics used in combination with direct communication of results to the prescribing physician by the laboratory or an antimicrobial stewardship team have shown that communication is essential for affecting outcomes (30)(31)(32)(33)(34)(35). The results of this combination were shorter length of stay (30,32,35,36), shorter time to switch to a ␀-lactam antibiotic (30-32, 35, 36), and decreased mortality (35).…”
Section: Discussionmentioning
confidence: 99%
“…Poor standardization of reporting leads to variation in test result formatting between health care facilities, which may result in physician confusion, leading to inaction or inappropriate action. As exhibited in one study, introduction of a rapid PCR-based system for the identification of staphylococcal bloodstream infections reduced the time to organism identification, but there was no significant benefit to patient outcome or time to optimal antimicrobial therapy (6). Alternatively, rapid testing enables physicians to initiate pathogen-directed therapy in shortened time frames, provided the results are interpreted correctly.…”
mentioning
confidence: 96%